Cultural adaptation of INDIGO mental health stigma reduction interventions using an ecological validity model in north India - Daniel, Mercian; Kallakuri, Sudha; Gronholm, Petra C.; Wahid, Syed Shabab; Kohrt, Brandon; Thornicroft, Graham; Maulik, Pallab K. (Frontiers in Psychiatry, 2024)
Background The International Study of Discrimination and Stigma Outcomes (INDIGO) Partnership is a multi-country international research program in seven sites across five low- and middle-income countries (LMICs) in Africa and Asia to develop, contextually adapt mental health stigma reduction interventions and pilot these among a variety of target populations. The aim of this paper is to report on the process of culturally adapting these interventions in India using an established framework. Methods As part of this larger program, we have contextualized and implemented these interventions from March 2022 to August 2023 in a site in north India. The Ecological Validity Model (EVM) was used to guide the adaptation and contextualization process comprising eight dimensions. Findings Six dimensions of the Ecological Validity Model were adapted, namely language, persons, metaphors, content, methods, and context; and two dimensions, namely concepts and goals, were retained. Conclusion Stigma reduction strategies with varied target groups, based on culturally appropriate adaptations, are more likely to be acceptable to the stakeholders involved in the intervention, and to be effective in terms of the program impact.